2012
DOI: 10.1007/s11357-012-9386-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on balance control in community-dwelling older women

Abstract: Older individuals have impaired balance control, particularly those that are frail and/or have sensory deprivations. Obese individuals show faster body sway during upright stance than normal weight individuals, suggesting that they also have difficulty controlling balance even if they do not have the same sensory issues as the older people. Therefore, the objective of this study was to examine if obesity is associated to a decreased balance control in older women. Postural sway of normal weight (n 015, age070.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
1
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 50 publications
4
74
1
21
Order By: Relevance
“…Therefore, obesity would be an additional postural constraint for stabilizing the base of support during a movement. Several studies have shown a close relationship between obesity and postural stability [3,4,[27][28][29][30]. Results of our study are in accordance with the literature and highlight that obese children have a less stable base in a standing position which affects the performance of a task requiring speed and precision.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, obesity would be an additional postural constraint for stabilizing the base of support during a movement. Several studies have shown a close relationship between obesity and postural stability [3,4,[27][28][29][30]. Results of our study are in accordance with the literature and highlight that obese children have a less stable base in a standing position which affects the performance of a task requiring speed and precision.…”
Section: Discussionsupporting
confidence: 91%
“…Alguns estudos utilizando plataforma de força avaliaram o tempo de manutenção em apoio estático unipodal. Observaram que indivíduos com IMC acima de 30 Kg/m² apresentaram redução no tempo de manutenção quando comparados com não obesos 12,13 . Outros estudos demonstraram atraso de 20 a 40% do impulso motor e sensorial sobre o nervo mediano, ulnar, fibular e tibial, quando comparado com sujeitos não obesos sugerindo redução do recrutamento de unidades motoras e da força muscular 14 .…”
Section: Discussionunclassified
“…Compared to non-obese subjects, the postural control of obese subjects may be more vulnerable [9,10], and after weight loss balance may improve [11]. Additionally, in patients with peripheral neuropathy from a variety of causes, those who are obese appear at the greatest risk for falling [12].…”
mentioning
confidence: 99%